(untitled) (International Journal of Applied Research in Management and Economics, 2023)
This study was conducted to investigate the effect of perceived value on customer loyalty by examining the mediating role of electronic word-of-mouth (eWOM) advertising and customer satisfaction (a Case study of Jabama Company). This research is applied objectively and it is a descriptive and survey study based on the data collection. The statistical population of the study is consisted of the customers of Jabama Company in Iran among which 200 customers were selected through the structural equation method as the sample size. The sampling method was simple random sampling. Furthermore, to measure the research variables and evaluate the research model, a 20-item questionnaire was designed and sent electronically to the members of the sample population. Correlational method and structural equation modeling were used to analyze the data. For this purpose, the Smart Pls3 software was applied and the Sobel Test used for testing the mediating hypotheses. The results of the study indicate that the perceived value on customer loyalty has a positive and significant impact by examining the mediating role of eWOM advertising and customer satisfaction.